Population of Nitrogen-Binding Bacteria to Bahia Grass (Paspalum notatum cv.competidor) Rhizosphere with Various Level of Nitrogen, Phosphor and Calcium Fertilizer - I K., Juliarta; Witariadi, N. M.; Suryani, N. N. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
The purpose of this study is to determine the population of nitrogen-binding bacteria to bahia grass ( Paspalum notatum Cv. Competidor) rhizosphere with various level of nitrogen, phosphor, and calcium fertilizer. The study was conducted for 15 weeks. The design used was Completely Randomized Design with three replicates and ten treatments so that there were 30 pots and soil samples with various level of N, P, and Ca fertilizer combinations, i.e., without fertilization or control, 100; 150; 200 kg/ha N, 50; 100 kg/ha P, and 50; 100 kg/ha Ca combined with prescribed treatment. The variables observed were TPC, total N fixing bacteria, nitrogen content, root dry weight, and root volume. According to the results of this research showed that in P0 treatment for  TPC and total N fixing bacteria with an average of 5.27 x 106 cfu / g and 4.07 x 106 cfu / g  have the most bacteria involved, so does for N content in P0 treatment with an average of 0.14 ppm is giving the highest N of value. Variable characteristics of the growth of Pasmalum notatum Cv. Competidor grass respectively have optimal results on treatment N 150 P 50 Ca 50 , among others, dry weight of kroots with an average of 3.50 g, root length with an average of 88.37 cm and root volume with an average of 15.93 g. Based on this research, it could be conclude that increasing in distribution of N fertilizer will reduce the total activity of bacteria population and the total population of N binding bacteria, however, the distribution of N fertilizer could be regenerate by distribution of P and Ca fertilizer. The N volume will lower in the combination of N, P and Ca fertilizers compared with no fertilization. The best growth characteristics of bahia grass will be gain by using N 150 P 50 Ca 50 fertilizer.   Keywords: Nitrogen-Binding Bacteria, Rhizosphere, Fertilizer Combination, Growth Charateristic